Estimation Earthquake Source Parameters in Mentawai Island Region Using Moment Tensor - Fahmia Zuwidhatul Husna; Sungkono; Muhammad Nurul Fahmi; Eko Minarto; Saifuddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
The Mentawai Islands is a seismically active zone that often experiences earthquakes due to the interaction of tectonic plates, so it is necessary to analyze the earthquake source parameters to understand its characteristics. This study aimed to determine earthquake source parameters for events of M w ≥ 5.5 that oc-curred in 2023 using moment tensor inversion. Three-component waveform data from the GEOFON network were analyzed in the time domain, filtered within a frequency range of 0.01 to 0.025 Hz. The inversion yielded variance reduction (VR) values above 70% (88.24%, 81.98%, 94.05%, and 73.16%), indicating a good fit between observed and synthetic waveforms. The results of waveform data analysis show that the earthquake in the study area was caused by tectonic activity characterized by the percentage of Double-Couple (DC) more dominant than Compensated Linear Vector Dipole (CLVD), at shallow depths. Comparison with earthquake catalogs (GCMT, USGS, and GFZ) showed agreement, supported by Kagan angle values below 60◦. In addition, the focal mechanism of the waveform data analysis indicated that the type of fault that causes the earthquake in the study area was a reverse fault.